The unexplored role of sedentary time and physical activity in glucose and lipid metabolism‐related placental mRNAs in pregnant women who are obese: the DALI lifestyle randomised controlled trial. (1st November 2021) - Acosta‐Manzano, P; Leopold‐Posch, B; Simmons, D; Devlieger, R; Galjaard, S; Corcoy, R; Adelantado, JM; Dunne, F; Harreiter, J; Kautzky‐Willer, A; Damm, P; Mathiesen, ER; et al.
Abstract : Objective: We aimed to explore: (i) the association of sedentary time (ST) and physical activity (PA) during pregnancy with the placental expression of genes related to glucose and lipid metabolism in pregnant women who are obese; (ii) maternal metabolic factors mediating changes in these placental transcripts; and (iii) cord blood markers related to the mRNAs mediating neonatal adiposity. Design: Multicentre randomised controlled trial. Setting: Hospitals in nine European countries. Population: A cohort of 112 pregnant women with placental tissue. Methods: Both ST and moderate‐to‐vigorous PA (MVPA) levels were measured objectively using accelerometry at three time periods during pregnancy. Main outcome measures: Placental mRNAs (FATP2, FATP3, FABP4, GLUT1 and PPAR‐γ) were measured with NanoString technology. Maternal and fetal metabolic markers and neonatal adiposity were assessed. Results: Longer periods of ST, especially in early to middle pregnancy, was associated with lower placental FATP2 and FATP3 expression ( P  < 0.05), whereas MVPA at baseline was inversely associated with GLUT1 mRNA ( P  = 0.02). Although placental FATP2 and FATP3 expression were regulated by the insulin–glucose axis ( P  < 0.05), no maternal metabolic marker mediated the association of ST/MVPA with placental mRNAs ( P  > 0.05). Additionally, placental FATP2 expression was inversely associated with cord blood triglycerides and free fatty acids (FFAs; P  < 0.01). No cord blood marker mediated neonatal adiposity except for cord blood leptin, which mediated the effects of PPAR‐γ on neonatal sum of skinfolds ( P  < 0.05). Conclusions: In early to middle pregnancy, ST is associated with the expression of placental genes linked to lipid transport. PA is hardly related to transporter mRNAs. Strategies aimed at reducing sedentary behaviour during pregnancy could modulate placental gene expression, which may help to prevent unfavourable fetal and maternal pregnancy outcomes. Tweetable abstract: Reducing sedentary behaviour in pregnancy might modulate placental expression of genes related to lipid metabolism in women who are obese. Tweetable abstract: Reducing sedentary behaviour in pregnancy might modulate placental expression of genes related to lipid metabolism in women who are obese.